Gene‐disruption of the entomopathogenic fungus Beauveria bassiana incubated with dsRNA. (13th May 2021) - Shin, Tae Young; Lee, Mi Rong; Lee, Se Jin; Kim, Jong Cheol; Kim, Sihyeon; Park, So Eun; Kim, Woo Jin; Kim, Jae Su
Abstract: The species of Beauveria bassiana is widely used for the management of agricultural insect pests. In this study, we integrated egfp ‐double‐stranded RNA (dsRNA) to a previously generated egfp ‐expressing B. bassiana transformant (Bb‐egfp#3) using a protoplast integration method. The Bb‐egfp#3 protoplast was mixed with the dsRNA under PEG/CaCl2 conditions and liquid‐cultured in Sabouraud dextrose broth for 5 days. A control culture followed the same procedure without dsRNA. Bb‐egfp#3/ egfp ‐dsRNA cultures showed very low fungal growth (OD630  = 0.2) compared to the control culture, Bb‐egfp#3 only (OD630  = 1.1). Screening of possible transformants on Sabouraud dextrose agar revealed a transformant T3, without egfp signal. T3 was confirmed as B. bassiana through sequencing of conserved genes and insect bioassays. Interestingly, the genomic egfp fragment of T3 was disrupted, and the egfp signal was not detected over four subcultures, which was also confirmed by RNA‐seq of Bb‐egfp#3 and T3. This study provides an interesting observation that protoplast integration with dsRNA could possibly generate significantly reduced gene expression in B. bassiana and it is stable across several generations.